QUALITY ASSESSMENT AND NUTRIENT ANALYSIS OF FREEZE-DRIED GRAPE SEED AND PEEL POWDERS - SARANYA S. MENON *; CHINNAPPAN A KALPANA (The Journal of Research ANGRAU, 2024)
The study conducted in the year 2023 aimed to develop freeze-dried grape seed and peel powder and evaluate its quality parameters and nutrients. Sun-dried grape seed and peel powder were also developed with a significant focus on comparision with freeze-dried samples, taking into account the economic feasibility and popularity of sun drying as compared to freeze-drying. Grape seed and peel were separated manually. The seed and peel were freeze-dried and stored in a freezer and sun-dried samples were kept in airtight containers. The quality parameters, nutrient composition, and sensory characteristics of both the freeze-dried and sun-dried grape peel and seed powder were examined. Quality parameters assessed included colour, solubility, pH and sensory attributes. Nutrients analysed included ascorbic acid by dye method, iron, phosphorus and carbohydrates by colorimetry. It was observed that freeze-dried grape seed and peel powders retained more colour, while freeze-dried grape peel powder had the highest solubility (67.22%). Both freeze-dried and sun-dried grape seed and peel powder exhibited an acidic pH (3.97,5.25,4.23 and 5.06). Freeze-dried grape peel powder was found to be rich in ascorbic acid (113.49 mg). Sun-dried grape seed and freeze-dried grape peel powders were found to havehigh phosphorus content (123.33 mg) and 108.33 mg, respectively), whereas,sun-dried grape seed featured the highest iron content (25.83 mg). Freeze-dried grape seed and peel powders were superior to sun-dried powder in quality and nutrients and hence can be used for manufacturing nutraceuticals.